Optical, morphology and electrical properties of In2O3 incorporating acid-treated single-walled carbon nanotubes based DSSC. (28th January 2016) - Mahalingam, S; Abdullah, H; Ashaari, I; Shaari, S; Muchtar, A
Abstract: This study focuses on the influence of an acid treatment process of single-walled carbon nanotubes (SWCNTs) in In2 O3 -based dye-sensitized solar cells (DSSCs). Pure In2 O3, In2 O3 -SWCNTs with acid treatment and In2 O3 -SWCNTs without acid treatment were prepared using the sol–gel method via a spin coating technique annealed at 450 °C. The optical, morphology and electrical properties of the photoanodes were characterized by means of UV–Vis analysis, atomic force microscopy and field-emission scanning electron microscopy, and J – V curve measurements, respectively. The optical band gap obtained through UV–Vis analysis showed that the acid treatment process modified the band gap of the photoanode, which enhances the V oc of the DSSCs. In addition, In2 O3 -SWCNTs with acid treatment possess a porous structure that improves the power conversion efficiency (PCE) of the DSSCs. In addition, the diameter of acid-treated SWCNTs was reduced compared to pristine SWCNTs. In2 O3 -SWCNTs with acid treatment exhibited the highest PCE of 1.40% with J sc of 7.6 mA cm −2, V oc of 0.51 V, and fill factor of 0.36. The increment in V oc is due to the higher band gap obtained through the UV–Vis absorption spectrum. Moreover, In2 O3 -SWCNTs with acid treatment has a higher electron lifetime with a higher effective diffusion coefficient that slows down the recombination rate and speeds up the electron transport process.